Land-Sea Interactions in Realisation of Ecosystem Approach in the Marine Spatial Planning in the Baltic Sea Region – Polish Perspective - Tomasz Bąkowski; Maciej Nyka (Review of European and Comparative Law, 2022)
Maritime spatial planning has become on of the fundamental instruments of managing human activity at the sea. It is mostly due to the rising competition for marine space, which is a consequence of rising number and variety of uses of the sea. Among the principles of marine spatial planning ecosystem approach as well as the taking into account the interaction between land and sea seem to play the most important role. First one is more general and axiological in it’s nature, while the second functions more as technical guide for planners. Together they can be called guiding principles of marine spatial planning. Ecosystem approach is a concept closely related to ecosystem services. It’s main aim is to sustain the productivity of ecosystems in the field of ecosystem services, what is often connotated with the health of the marine ecosystem. Multiple correlations between land and sea can be easily seen in the managerial goals of the marine ecosystem. Trophic relations seems to be reflected in legal regulations, but the question remains if the marine spatial planning regime really reflects the interactions between land and the sea.